Profile of patients of the Geriatric Home care Program of a Costa Rican Geriatric Hospital - Picado-Ovares, José E. (2021)
Profile of patients of the Geriatric Home Care program of a Costa Rican Geriatric Hospital. The Geriatric Community Care Unit of the Hospital Nacional de Geriatría y Gerontología visits older adults with terminal illnesses by an interdisciplinary team. In Each patient is assessed by a multidisciplinary team. This is a descriptive study that describe the profile of the patients who have entered the ACG program, from January 2012 to June 2020. An exploratory analysis is performed of 3361 patients evaluated by the Unit. Most patients come from the city of Desamparados. The average age was 83,7. They are severe dependents; Most are women widowers. Dementia syndromes represent the most prevalent cause of admission, followed by neoplastic pathology. Patients have polypharmacy, neurobehavioral disorders, dysphagia and nutritional disturbances predominating “nutritional risk” category. Few have bladder catheter, nasogastric tube and had grade 3 and 4 pressure ulcers. A compromised network is identified in most of the cases. Most of the caregivers are their children. Most of the patients analized in the study period in the Geriatric Community Care service are severe dependents, women and widowers. Dementia syndromes represent the most prevalent cause of admission to the program.